Sources, Distribution, and Health Risks of Heavy Metal Contamination in the Tongren Mercury Mining Area: A Case Study on Mercury and Cadmium - Shuo Wang; Yani Guo; Huimin Hu; Yingqi Liang; Kun Li; Kuifu Zhang; Guiqiong Hou; Chunhai Li; Jiaxun Zhang; Zhenxing Wang (Toxics, 2025)
This study assessed heavy metal contamination and associated health risks in soils and crops in the vicinity of a mercury mine located in Tongren, Guizhou Province, China, focusing on mercury (Hg), cadmium (Cd), arsenic (As), lead (Pb), and chromium (Cr). The study used the Index of Geological Accumulation (Igeo) and Health Risk Assessment (HRA) to quantify the level of contamination and assess the potential risks. The results showed that Area I was the most severely contaminated, with 94.24% of the sample sites being heavily contaminated with mercury, followed by Area II and Area III with severe cadmium contamination. The health risk assessment showed that children were exposed to non-carcinogenic risks of mercury and cadmium that exceeded the safety thresholds, with mercury being the major non-carcinogenic factor, especially through oral intake. The study also assessed the contribution of each heavy metal to pollution, with mercury contributing the most to ecological and health risks, especially in Areas I and III. The study highlights the urgent need to strengthen pollution control strategies, focusing on mining activities and agricultural inputs, to reduce risks and protect public health.